Continuing Care Bundle in Elderly Patients with Rectal Cancer after Radical Resection with Permanent Stoma. (8th August 2022) - Pan, Pan; Chen, Lei; Zhang, Dan; Rao, Shuang; Tao, Ying; Fan, Lin
Abstract : Objective . A continuing care bundle can achieve a better outcome than a single implementation after discharge. This study aims to investigate the effect of this intervention in elderly patients with rectal cancer after radical resection with a permanent stoma. Methods . Elderly patients diagnosed with rectal cancer underwent radical resection with permanent stoma, they were divided into the control group ( n = 42) and bundle group ( n = 42). The control group received the conventional care, and the bundle group received the continuing care bundle in addition to the conventional care. At 1- and 3-month after discharge, self-efficacy, self-care knowledge, ability to change stoma appliances, negative emotions, quality of life, and patient satisfaction were observed. Results . The increased levels of self-efficacy, self-care knowledge, and ability to change stoma appliances were displayed in the bundle group after discharge as compared with that in the control group, along with the enhanced score of SF-36 subscales, including physical function (PF), role physical (RP), global health (GH) and vitality (V), social function (SF), and mental health (MH). Furthermore, patients showed alleviated depression and anxiety after the continuing care bundle as compared to those after conventional care. Besides, the bundle groups had higher patient satisfaction than the control group. Conclusions . Continuing care bundle can serve as an effectiveness intervention in elderly rectal cancer patients after radical resection with permanent stoma via increasing self-efficacy and self-care knowledge, enhancing the ability to change stoma appliance, reliving the negative emotion, and improving quality of life and patient satisfaction.